Complementary Modernisms in China and the United States: Art as Life/Art as Idea - Zhang, Jian; Robertson, Bruce (punctum books, 2020)
Complementary Modernisms in China and the United States: Art as Life/Art as Idea is the result of a conference where Chinese and Americanist art historians addressed the development of modernism in their respective cultural traditions. The chapters juxtapose historical developments without attempting to map connections or influences. Instead, both national modernisms are presented as part of the larger terrain of global modernism, but generated within specific, localized circumstances. This juxtaposition reveals significant differences as much as any particular moments of connection or similarities, disrupting any standard narrative of the primacy of French (or European) avant-garde art and its influence on more belated and peripheral communities.The differences that are revealed are not merely the result of the very different historical trajectories of each country's moves into modernity. Rather, differences in attention and methodology are just as important, in particular the focus on the post-1980 development of Chinese art as part of the modernization of Chinese culture and economy, rather than the American perspective on post-1980s postmodern qualities. At the same time, significant convergent concerns emerge, such as the importance of urban centers and urbanization, the profound effect of political and technological disruption, and the question of identity.The volume represent a cross-section of Chinese and Americanist art historians, both early career and senior scholars, working on a wide variety of subjects, such as the Ashcan School, Impressionism, Cai Liang, Liang Sicheng, Huang Binhong, Cézanne, Bauhaus, Joseph Cornell, Andrew Wyeth, Louise Nevelson, Jackson Pollock, Andy Warhol, and contemporary art more broadly, with (as is usual in any survey of the 20th century these days) a concentration on the 1960s.《交互视野下的中国和美国的现代艺术: 艺术/生活或观念》这一会议论文集收录了中美艺术史家对现代主义在各自传统下的发展进行研究所得的成果。这些文章并置历史发展，而非试图详述其中的关联或影响。相反，两个国家的现代主义都被展现为全球现代主义大背景中的一部分，并被认为是在特定环境中产生的。这种并置显示了重要的差异性以及任何特殊情况下的联系或相似之处，打破了一般强调法国（或欧洲）先锋派首要地位及其对周围团体产生影响的标准论述。中国与美国现代主义发展上的差异，并不仅仅是由于两国进入不同历史轨道发展现代化而导致的。相反，关注点和方法论的差异也同样重要，尤其是关注八十年代后中国艺术的发展，将其作为中国文化与经济现代化的一部分，而不是从美国视角来看待八十年代后的后现代价值。同时，也出现了重要的趋同关注点：城市中心与城市化的重要性，政治或科技解体所造成的深远影响，以及自我认同的问题。本论文集所收录的文章，彰显了当今重要的中美艺术史家研究的多样性，从资深到青年一代，从阿什坎学派至当代艺术，（并与任何当下对二十世纪作出的概括论述相一致，）将重点放在二十世纪六十年代。